Evaluation of rubber powder waste as reinforcement of the polyurethane derived from castor oil. (October 2020) - Silva, Nycolle G.S.; Cortat, Lucas I.C.O.; Orlando, Diego; Mulinari, Daniella Regina
Graphical abstract: Highlights: Waste tire rubber (WTR) was used as an alternative filler in polyurethane (PU) foam. The WTR reinforced in PU influenced the morphological and mechanical properties. Chemical interactions of WTR and PU were confirmed by FTIR and XRD. The WTR reinforced in PU presented better thermal stability compared to pure PU. Abstract: Waste tire rubber is produced on a large scale in the automotive industry and is considered difficult to recycle because they have iron, nylon, polyester, and chemical structure formed by cross-links. In this way, the waste is almost always deposited in inappropriate places or incorrectly burned, causing a series of environmental problems. The objective of this work was to analyze the viability of the use of waste tire rubber (5, 10, and 20% m/m) reinforced in polyurethane foam (PU) derived from castor oil to obtain composites, as an alternative for raw materials petrochemical industrial. The materials were characterized by scanning electron microscopy (SEM), optical microscopy (OM), apparent density, contact angle, water absorption, X-ray diffractometry (XRD), spectroscopy infrared (FTIR), thermogravimetry (TGA) techniques, and mechanical tests. The results showed that the residue of the rubber powder reinforced with polyurethane caused an increase in the density of the composites when compared to pure PU, which directly influenced the morphological, physical, thermal, and mechanical properties. This fact occurred because with the insertion of rubber powder in the PU there was a decrease in cell size and increase of pore volume. The TG and DTG analyzes showed that the insertion of the rubber powder improved the thermal stability of the composite when compared to pure PU, as well as impact tests and contact angle.